Prevalence of caseous lymphadenitis in sheep and goats in east coast of Peninsular Malaysia and its pathogenesis in a mouse model - Osman, Abdinasir Yusuf (2012)
A cross-sectional study was conducted in Peninsular Malaysia with the objectives of determining the serological evidence and the management practices that could be associated with CLA distribution among sheep and goats in different geographical regions. The etiopathogenesis of CLA was also studied with the objectives of describing the clinical, pathological,hematological and biochemical alterations following intraperitoneal exposure of mice to whole bacterium and exotoxin extracted from C.pseudotuberculosis. In the coss-sectional study,all farmers had semi-extensive rearing system;27.6% (13/47) of farmers had periodical veterinary services; 10.6% (5/47) took note of animals with clinical signs of CLA; 14.8% (7/47) were aware of the zoonotic potential of this disease. It was apparent that lack of sanitary measures and epidemiological studies led to the dissemination of this disease in Malaysia. A total of 422 animals from 15 small ruminant farms (sheep and goats) in four states of East Coast of Peninsular Malaysia were screened during the period from January to April 2011.Agar gel precipitation test (AGPT) was conducted on serum samples collected from the animals. Forty seven samples out of 422 were positivefor CLA using AGPT test. The frequency of CLA infections was estimated at 11.1%. Management practices were analyzed through questionnaire. 224 mice, 2-3 weeks of old, were selected and divided into three groups, namely control, whole bacterium and exotoxin groups. Mice of the whole bacteriumgroup were exposed intraperitoneally to 1 ml of the inoculums containing 109colony-forming unit (CFU)/ml of live C. pseudotuberculosis. The exotoxingroup wasinjected intraperitoneally with a single dose of exotoxin extracted from C.pseudotuberculosis. The control group wasexposed intraperitoneally to 1 ml of phosphate buffered saline (PBS). The groups of exotoxin treated and whole bacterium challenged (C. pseudotuberculosis) showed prominent clinical signs that were characteristic of CLA, which included depression, anorexia, submandibular oedema, yellowish and bloody diarrhea, ruffledcoat, eye discharges, poorer general condition, and occasionally partial tremor of hindquarters. In necropsy, visceral abscess was the condition recorded in whole bacterium and exotoxin groups. There were also congestion and hemorrhages in the lungs, liver, spleen, kidney and intestine. Microscopically, there were lesions in the form of tuberculous granuloma (caseating tubercule), giant cells, infiltration of neutrophils and macrophages, degeneration, vacuolation (necrosis), haemorrhage, and microabscesses.Hematologically, there were significant decrease in Hb, thrombocytes count, and significant increase in WBC, neutrophils, monocytes counts in the infected group. There were also highly significant increases in the mean levels of CK,AST,ALP,and ALT. Phosphorus concentrations in the infected group were significant (p<0.05)compared to the control group.In the exotoxin and whole bacterium challenged groups, the concentrations of Serum Amyloid A (SAA), Haptogolbin (Hp), and α-1 Acid glycoprotein were significantly higher than in the healthy mice (control group). This study shows thatlittle attention has been given to this devastating disease (CLA) and its economic importance allowing existence of endemic nature of the disease in this country. In addition, the present study also indicates that C.pseudotuberculosis causes disturbances which leadto severe damages in visceral organs. Further epidemiological studies using reliable diagnostic tools, application of appropriate management practices, and extensive studies on blood picture and plasma proteins need to be carried out to eradicate this disease.